Improving Activity and Learning Outcomes Through the Student Team Achievement Divisions Learning Model for Elementary School Students - Natijatul Khusna; Yuli Widiyono; Muflikhul Khaq (Institut Agama Islam Negeri Palopo, 2023)
Learning mathematics is still considered a difficult thing for students. Therefore, the activity and learning outcomes of mathematics are still not optimal. Proper, interesting and fun learning needs to be done to obtain maximum learning outcomes. The purpose of this research is to increase the activeness and learning outcomes of mathematics through the STAD learning model. The type of research is classroom action research. Methods of collecting data by observation, interviews, and tests. The results showed that the activeness of learning the material of flat shapes has increased. The average learning activity in the first cycle was 73.26% with the moderately active category, in the second cycle it increased to 87.85% with the active category. The increase in student activity from cycle I to cycle II was 14.58%. The average student learning outcomes in the first cycle was 73, then in the second cycle increased to 85.6. The conclusion of this study is that the use of the STAD learning model can increase the activity and learning outcomes of mathematics in the fourth grade elementary school flat-building material.